A Family of 12‐Azametallacrown‐4 Structural Motif with Heterometallic MnIII‐Ln‐MnIII‐Ln (Ln=Dy, Er, Yb, Tb, Y) Alternate Arrangement and Single‐Molecule Magnet Behavior. Issue 41 (21st August 2015) - Yang, Hua; Cao, Fan; Li, Dacheng; Zeng, Suyuan; Song, You; Dou, Jianmin
Abstract Mixed 3d–4f 12‐azametallacrown‐4 complexes, [Mn2Ln2(OH)2(hppt)4(OAc)2(DMF)2]⋅2 DMF⋅H2O [Ln=Dy (1), Er (2), Yb (3), Tb (4) and Y (5), H2hppt=3‐(2‐hydroxyphenyl)‐5‐(pyrazin‐2‐yl)‐1, 2, 4‐triazole)], were synthesized by reactions of H2hppt with Mn(OAc)2⋅4 H2O and Ln(NO3)3⋅6 H2O. This is the first 3d–4f azametallacrown family to incorporate Ln ions into the ring sets. These isostructural complexes exhibit alternating arrangements of two Mn and two Ln ions in the rings with each pair of metal centers bound by an NN group and μ2‐O bridging. Magnetic measurements revealed dominant antiferromagnetic interactions between metal centers, and frequency‐dependent out‐of‐phase (<alternatives> <![CDATA[χ ^′^′_M ]]> <inline-graphic xlink:href="ark:/27927/pgj2sff50tw" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>) signals below 4 K suggest slow relaxation of magnetization.